The role of political orientation in shaping deservingness perceptions and immigration attitudes in Europe: A multilevel analysis - Häkkilä, Laura; Kouvo, Antti-Jussi; Oinas, Tomi; Pfeifer, Michael; Toikko, Timo (Cambridge University Press (CUP), 2025)
In this study, we focus on European immigration attitudes in the perspective of deservingness perceptions and political orientation. Our data are conducted from the European Social Survey (2016) database, which contains 21 European countries and 39,400 participants. We used the multilevel method to study the relationship between immigration attitudes and deservingness perceptions. The results demonstrate that the more negative deservingness perceptions are, the more negative immigration attitudes more likely become. Moreover, country-level political orientation moderate the relationship between immigration attitudes and deservingness perceptions. Deservingness perceptions have a greater role in explaining immigration attitudes on countries with political left-context, which gives us a new perspective to understand the public debates about immigration.